The level of student independence in using YouTube to improve computer assembly skills at Vocational High School - Khatrin Juliani Taku Neno (Universitas Putra Indonesia YPTK Padang, 2023)
This research aims to determine the level of achievement in aspects of implementation, understanding of learning, and student learning success in using YouTube independently to improve computer assembly skills in class XI students in the Computer Network and Telecommunications Engineering skills program at SMKN 6 Kupang. This research is a quantitative descriptive type. The research population was 60 class XI students. Data was taken using a closed questionnaire. The instrument was validated with Expert Judgment, while Crobanch Alpha was used to find reliability values. The data obtained was analyzed using descriptive statistics in the form of mean values. The research results show: (1) The learning process using YouTube as a learning resource can increase learning independence with an achievement level of 93.49%. (2) Using YouTube can increase understanding of computer assembly procedures with an achievement level of 96.38%. (3) Utilizing YouTube can improve computer assembly skills with an achievement level of 97.40%.